2014
DOI: 10.1210/me.2013-1288
|View full text |Cite
|
Sign up to set email alerts
|

Notch Signaling Regulates Ovarian Follicle Formation and Coordinates Follicular Growth

Abstract: Ovarian follicles form through a process in which somatic pregranulosa cells encapsulate individual germ cells from germ cell syncytia. Complementary expression of the Notch ligand, Jagged1, in germ cells and the Notch receptor, Notch2, in pregranulosa cells suggests a role for Notch signaling in mediating cellular interactions during follicle assembly. Using a Notch reporter mouse, we demonstrate that Notch signaling is active within somatic cells of the embryonic ovary, and these cells undergo dramatic reorg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
125
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(134 citation statements)
references
References 73 publications
9
125
0
Order By: Relevance
“…TGF-␤ signaling could regulate testis formation and male germ cell development (9). Notch signaling was reported antagonistically to regulate germ line stem cell niche formation in Drosophila male embryonic gonads (19) and deletion of Jagged1, a Notch ligand, could lead to the formation of multicystic follicles in the mouse ovary (20). These reports provide support that our selected candidate key signaling pathways play an important role in the differentiation of the male germ cells.…”
Section: Discussionsupporting
confidence: 67%
“…TGF-␤ signaling could regulate testis formation and male germ cell development (9). Notch signaling was reported antagonistically to regulate germ line stem cell niche formation in Drosophila male embryonic gonads (19) and deletion of Jagged1, a Notch ligand, could lead to the formation of multicystic follicles in the mouse ovary (20). These reports provide support that our selected candidate key signaling pathways play an important role in the differentiation of the male germ cells.…”
Section: Discussionsupporting
confidence: 67%
“…A functional role for Notch signaling in controlling primordial follicle formation has recently been reported (Trombly et al, 2009;Vanorny et al, 2014;Xu and Gridley, 2013). As an upstream regulator of Notch signaling, ADAM10 might play a similar role in regulating the formation of primordial follicles according to our findings.…”
Section: Adam10 Regulates the Recruitment And Differentiation Of Pregsupporting
confidence: 79%
“…To assess whether ADAM10 is required in vivo for folliculogenesis, we conditionally deleted ADAM10 in a somatic lineage of perinatal ovaries using an anti-Müllerian hormone type 2 receptor-Cre (Amhr2-Cre) mouse line (Jamin et al, 2002), which mediates the expression of CRE recombinase in somatic cells of ovaries from 12.5 dpc (Jamin et al, 2002;Jorgez et al, 2004;Vanorny et al, 2014). qRT-PCR analysis of ovaries showed that the levels of Adam10 mRNA in Amhr2-Cre; Adam10 f/d ovaries was 52.8% that of control littermates (Fig.…”
Section: Deletion Of Adam10 In Vivo Disrupts the Formation Of Primordmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas in the Drosophila ovary the Notch receptor is expressed in the niche, the receptor is required in the germ line stem cells in C. elegans. In rodent ovaries, Notch2 is expressed in granulosa cells and the Jag1 ligand is expressed in the germ cells (Johnson et al, 2001;Vanorny et al, 2014;Xu and Gridley, 2013). The ovary of sexually mature virgin N1IP::Cre HI ; Rosa +/R26R females showed ubiquitous labeling in granulosa cells (Fig.…”
Section: Resultsmentioning
confidence: 98%